Design calculation of heat exchangers - Khasanov H.G, Yakubov U.K (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In order to take the right amount of energy from an environment with low potential heat, it is necessary to use very large volumes of this very environment. In order to organize a relatively efficient heat exchange, it will be necessary to move sufficiently large amounts of secondary coolant over very long distances.